Review of Prognostic Testing for Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Pakeltytė, Donata; Burnytė, Birutė (Neurologijos seminarai, 2024)
Frontotemporal dementia and amyotrophic lateral sclerosis are neurodegenerative diseases with distinc clinical presentation, but interconnected with each other. Frontotemporal dementia most often presents as behavioural or speech impairment, whereas amyotrophic lateral sclerosis presents as progressive weakness of voluntary muscles. C9orf72 repeat expansion is the most common genetic cause of both diseases although there are more causative genes for these diseases separately. As the knowledge of frontotemporal dementia and amyotrophic lateral sclerosis is expanding, more relatives of affected patiens inquire about prognostic testing. Unfortunatelly, there are no definitive recommendations for prognostic testing and because of partial penetrance of causative gene variants and unknown genetic cause of high number of cases, clinical interpretation of prognostic testing is complicated.This article provides review of recommendations and limitations of prognostic testing for frontotemporal dementia and amyotrophic lateral sclerosis.
Keywords: prognostic genetic testing; amyotrophic lateral sclerosis; frontotemporal dementia; C9orf72 repeat expansion